Academic Supervision by School Supervisors in the Merdeka Belajar Paradigm to Achieve High School Students' Learning Achievements in East Manggarai Regency, NTT - Leonardus Jafar; Achmad Ridwan; Mahdiyah (Green Publisher Indonesia, 2026)
This study explores the role of academic supervision conducted by school supervisors within the Merdeka Belajar paradigm and its contribution to improving high school students’ learning achievement in East Manggarai Regency, Nusa Tenggara Timur. Using a mixed-method approach with the CIPP evaluation model, this research combines quantitative and qualitative data to obtain comprehensive insights regarding the implementation, impact, and challenges of academic supervision. The findings reveal that academic supervision has been carried out systematically and contextually, beginning with needs analysis, collaborative planning, and implementation through coaching, mentoring, observation, and reflective dialogue. Supervision contributes to improving the quality of teaching practices, classroom management, teacher professionalism, student engagement, and the tendency of improved learning outcomes. Teachers also perceive academic supervision positively, acknowledging its role in strengthening planning, instructional strategies, and formative assessment. However, the study also identifies several constraints, including varied teacher understanding of Merdeka Belajar, limited facilities, administrative burden, uneven implementation, and insufficient follow-up support, resulting in learning achievements that have not yet been evenly improved across schools. Overall, academic supervision remains a strategic instrument to support the implementation of Merdeka Belajar and enhance student learning achievement, but it requires more consistent, contextual, and sustainable strengthening through improved mentoring, capacity building, and policy support.